2018
DOI: 10.1111/apce.12192
|View full text |Cite
|
Sign up to set email alerts
|

Public Private Partnerships in Europe for Building and Managing Public Infrastructures: An Economic Perspective

Abstract: Public–private partnerships (PPPs) are long‐term contractual agreements between the public and private sector for the provision of public infrastructures and services. Due to tighter budget constraints and to a renewed interest in greater involvement of the private sector in the provision of public services, PPPs are likely to grow in the near future. In this paper, we review the theory and practice of PPPs, highlighting their potential role as well as discussing the main factors influencing the likelihood of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…It is worth noticing that Chou et al [42] acknowledges existing negative effects of such collaboration, as disputes may occur during contract management. However, a research from Cheung et al [43] highlights the PPP benefits on mitigating the shortage of governmental funding and avoid public investment restriction in the UK Most EU member states and also considers the PPPs as an important tool to attract additional financial resources [44] and, overall, the years to come we will find an increasing role for PPPs in the provision of public infrastructures and services [45]. We have also noticed a lack of research in recent years concerning the governmental process digitalization, when compared with the AI that has gained strength.…”
Section: The Digital Scope and The Shift To Artificial Intelligencementioning
confidence: 99%
“…It is worth noticing that Chou et al [42] acknowledges existing negative effects of such collaboration, as disputes may occur during contract management. However, a research from Cheung et al [43] highlights the PPP benefits on mitigating the shortage of governmental funding and avoid public investment restriction in the UK Most EU member states and also considers the PPPs as an important tool to attract additional financial resources [44] and, overall, the years to come we will find an increasing role for PPPs in the provision of public infrastructures and services [45]. We have also noticed a lack of research in recent years concerning the governmental process digitalization, when compared with the AI that has gained strength.…”
Section: The Digital Scope and The Shift To Artificial Intelligencementioning
confidence: 99%
“…This scheme is also adopted in railway projects worldwide to release state budgets through a cost-sharing scenario from the private sector. Some countries, such as in the western part of Europe and Japan, heavily depend on a market based on private investment [28,29]. While in some others, mainly from developing countries such as Indonesia, the railway is part of public interest, thus should be managed by the government or representation of the state [30,31].…”
Section: Public-private Partnership In Railway Projectsmentioning
confidence: 99%
“…The benefits of negotiation during the selection stage are also emphasized by (Decio Coviello, Andrea Guglielmo and Giancarlo Spagnolo, 2017). With a regression discontinuity design analysis to document the causal effect of increasing buyers' discretion on procurement outcomes in a large database for public 8 This section relies on Iossa and Saussier (2018). works in Italy, they found that discretion increases the probability that the same firm wins repeatedly, but it does not deteriorate the procurement outcomes.…”
Section: Box 5: Privatization and Mortalitymentioning
confidence: 99%